A Comparative Analysis of the Quality of Islamic and Conventional Banksâ Asset Management in Indonesia - Abd. Majid, M. Shabri; Musnadi, Said; Putra, Indra Yadi (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2014)
This research empirically and comparatively examines the quality of conventional and Islamic banksâ asset management in Indonesia during the period 2009-2011. Four general conventional banks [i.e., Bank Mandiri Indonesia (BMI), Bank Rakyat Indonesia (BRI), Bank Central Asia (BCA), and Bank Nasional Indonesia (BNI)] and four Islamic banks (Bank Muamalat, Bank Syariah Mandiri, Bank Syariah Mega Indonesia, and Bank Syariah BRI) were, respectively, explored. Specifically, the purpose of this study is to compare the quality of the Islamic and conventional banksâ asset management with the CAMEL (capital, asset, management, earning, and liquidity) method. It also attempts to analyse the influences of the ROA (Return on Asset), TLTA (Total Loan to Total Assets), and OITL (Operating Income to Total Liabilities) on the quality of the banksâ asset management. The CAMEL method was used to evaluate the quality level of the banksâ asset management, while the multiple regression analysis was then adopted to explore the determinants of the quality of the banksâ asset management. The study documented that Bank Syariah BRI was the best performing bank, with the highest CAMEL score of 50.33, while Bank Mandiri Indonesia was the worst performer with the lowest CAMEL score of 26.33. As a group, the Islamic banks were found to have better rankings, i.e., positions 1, 2, 3, and 6, while the conventional banks were found in 4, 5, 7, and 8, respectively. The study proved that the Islamic banks have a better asset management quality compared to their conventional counterparts. The Islamic banks were also proved to be better able to withstand the risks, particularly the financing risk.Â Â Â Â Â Â